2015
DOI: 10.1080/13548506.2015.1112413
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory focus and adherence to self-care behaviors among adults with type 2 diabetes

Abstract: The aims of this study were, first, to test the association between regulatory focus of adults with type 2 diabetes and their adherence to two types of self-care behaviors - lifestyle change (e.g. physical activity and diet) and medical care regimens (blood-glucose monitoring, foot care and medication usage). Second, to explore whether a fit between the message framing and patients' regulatory focus would improve their intentions to adhere specifically when the type of behavior fits the patients' regulatory fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 34 publications
6
31
2
Order By: Relevance
“…This supports the idea that one person can hold different motives that coexist and together drive behaviour (see Ingledew & Markland, 2008;Ingledew et al, 2009;Teixeira et al, 2012, for similar considerations). Moreover, regulatory focus framing per se did not produce any main effect, which is congruent with a large body of literature showing that the regulatory focus effects are seldom direct but most often moderated by another factor (e.g., Avraham et al, 2016;Berezowska et al, 2017;Florack et al, 2013).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This supports the idea that one person can hold different motives that coexist and together drive behaviour (see Ingledew & Markland, 2008;Ingledew et al, 2009;Teixeira et al, 2012, for similar considerations). Moreover, regulatory focus framing per se did not produce any main effect, which is congruent with a large body of literature showing that the regulatory focus effects are seldom direct but most often moderated by another factor (e.g., Avraham et al, 2016;Berezowska et al, 2017;Florack et al, 2013).…”
Section: Discussionsupporting
confidence: 84%
“…Individuals adopt more behaviours that are supposed to be beneficial for their health when the persuasion message fits with the person's focus: participants reported a greater intention to increase their fruits and vegetables intake when an eagerness (vigilance) message framing matched their promotion (prevention) focus (Cesario et al, 2004), and when the emphasis was put on benefits versus costs, respectively (Spiegel, Grant-Pillow, & Higgins, 2004). Similarly, intention to adhere to medical care regimens was higher amongst prevention-oriented patients when the message framing fit their orientation (Avraham et al, 2016). Regulatory focus also interacts with temporal distance of the highlighted health outcomes: a promotion focus increases intention and behaviour when distant outcomes are highlighted whereas a prevention focus proves more efficient when immediate outcomes are highlighted (Berezowska et al, 2017).…”
Section: Regulatory Focus and Fit And Health Behaviourmentioning
confidence: 99%
“…Similar findings have been observed for physical activity and making dietary changes (de Bruijn et al, 2014;van Assema et al, 2001), and health behaviours more generally (Avraham et al, 2016).…”
Section: Discussionsupporting
confidence: 74%
“…Although this review has demonstrated that there is insufficient evidence to support motivational interviewing to improve adherence in this population, its efficacy in other conditions suggests that further research is warranted . Studies have demonstrated motivational interviewing to effectively enhance adherence to physical activity, healthy eating, alcohol intake, and medication adherence to improve control of long term‐conditions such as hypertension, diabetes, or HIV . The measurement of effectiveness in these studies is facilitated by having clearly defined behavioural or physiological targets based on evidence of efficacy, for example known levels of physical activity to reduce risk.…”
Section: Discussionmentioning
confidence: 99%